Analisis Kesalahan Berbahasa Penulisan Surat Lamaran Pekerjaan Siswa SMK Al-Huda Bumiayu - Yeyen Yuniar; Nur Azizah; Cintya Nurika Irma (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
The purpose of this study is to analyze the language errors contained in the job application letter of SMK Al-Huda Bumiayu students. The method used in this research is descriptive method.This study uses data triangulation aimed to test the validity of the data. The analysis technique in this study uses three ways namely data reduction, data presentation, and drawing conclusions. Error writing job application letter written by Al-Huda Bumiayu Vocational School student Language errors found were (1) errors in writing prepositions, (2) errors in writing standard words, (3) errors in italics, and (4) mistakes in capital letters.